2022
DOI: 10.3390/pr10050903
|View full text |Cite
|
Sign up to set email alerts
|

Circular Economy Indicators for the Assessment of Waste and By-Products from the Palm Oil Sector

Abstract: A circular economy (CE) promotes the reuse, reincorporation and valuation of waste and by-products under the framework of sustainable development through models and indicators that evaluate scenarios of second use and reduction in non-incorporated outputs to reduce negative externalities and pressures on the dimensions of development. A CE model applied to the transformation process of RFF in agro-industries is developed, which consists in the identification of the residue coefficients of EFB (22.48% ± 0.8), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…This approach advocates for a self-sustaining system that not only stimulates economic advancement but also facilitates the preservation of the environment [25,26]. This approach is supported by models and indicators designed to assess the sustainability and economic viability of circular economy practices, highlighting the potential for cost savings and emission reductions [27].…”
Section: Ce Principles and Their Relevance To The Palm Oil Industrymentioning
confidence: 99%
“…This approach advocates for a self-sustaining system that not only stimulates economic advancement but also facilitates the preservation of the environment [25,26]. This approach is supported by models and indicators designed to assess the sustainability and economic viability of circular economy practices, highlighting the potential for cost savings and emission reductions [27].…”
Section: Ce Principles and Their Relevance To The Palm Oil Industrymentioning
confidence: 99%
“…This is achieved through the utilization of models and indicators that assess scenarios involving secondary utilization and a reduction in unincorporated outputs. These measures aim to mitigate negative externalities and reduce pressures on various dimensions of development [19]. This concept focuses on efficient utilization of resources, waste reduction, and regeneration of natural resources.…”
Section: Figure 1 Differences Between Linear Economy and Ce [17]mentioning
confidence: 99%
“…This biomass comprises elements like EFB, oil palm fronds (OPF), oil palm trunks (OPT), palm kernel cakes (PKC), and palm oil mill effluent (POME), as outlined by Boonsawang and Youravong [46]. Study by Bejarano et al [47] reported that merely 23% of waste and by-products from agro-industry are recycled back into the production process, leaving the bulk of these resources untapped. A breakdown of the weight percentage of these oil palm elements is shown in Figure 4 [48].…”
Section: Oil Palm Wastementioning
confidence: 99%